Mechanical Analysis of Reliable Communication in the Alternating Bit Protocol Using the Maude Invariant Analyzer Tool (2014)
The InvA tool supports the deductive verification of safety properties of infinite-state concurrent systems. Given a concurrent system specified as a rewrite theory and a safety formula to be verified, InvA reduces such a formula to inductive properties of the underlying equational theory by means of the application of a few inference rules. Through the combination of various techniques such as unification, narrowing, equationally-defined equality predicates, and SMT solving, InvA achieves a significant degree of automation, verifying automatically many proof obligations. Maude Inductive Theorem Prover (ITP) can be used to discharge the remaining obligations which are not automatically verified by InvA. Verification of the reliable communication ensured by the Alternating Bit Protocol (ABP) is used as a case study to explain the use of the InvA tool, and to illustrate its effectiveness and degree of automation in a concrete way.